Killer Words: A New Approach to the Issue of the Repression of Freemasonry During the Spanish Civil War and the Franco Regime - Morales Ruiz, Juan José (2019)
In this article I study the repression of Freemasonry during the Spanish civil war and the Franco regime, through an analysis of the anti-Masonic discourse published during this historical period, which I address in my book “Killing Words”. I argue that a discourse against Freemasonry was developed during those periods that sought the moral annihilation of the Freemasons, in addition to the brutal physical repression that took place. Such words were words that hurt and kill, they were killer words, as I discussed in this article.